Sosialisasi dan Pelatihan Pengolahan Telur Asin Bebek dan Burung Puyuh di Perumahan Griya Betungan Asri Kota Bengkulu - Widawati, Lina; Andriani, Evi; Fariadi, Herri; Perata, Lusita Dian; Sihite, Devi Monika (Jurnal Dehasen Mengabdi, 2023)
Eggs are a source of animal protein which tastes good and delicious, easy to digest and highly nutritious. The weakness of eggs is that they are easily damaged, so one way of preserving them that doesn't change their nutrition is salting them. Salted eggs which are often found in traditional markets or supermarkets are original products of the Indonesian people which are done in a Home Industry. The purpose of the socialization and salted egg processing training is to improve soft skills and skills for PKK mothers at Griya Betungan Asri Housing, Bengkulu City. Socialization and training on turning duck eggs and quail eggs into salted eggs is carried out through education, training and application in the Community Service program. By holding this socialization and training, the knowledge and skills of PKK mothers in Griya Betungan Asri Housing, Bengkulu City, regarding technology processing and packaging of salted duck and quail egg products. As well as increasing the knowledge and skills of PKK women in Griya Betungan Asri Housing, Bengkulu City regarding label design and product packaging